Nonlinear Dispersive Model of Electroporation for Irregular Nucleated Cells. Issue 5 (9th June 2019) - Chiapperino, Michele Alessandro; Bia, Pietro; Caratelli, Diego; Gielis, Johan; Mescia, Luciano; Dermol‐Černe, Janja; Miklavčič, Damijan
Abstract : In this work, the electroporation phenomenon induced by pulsed electric field on different nucleated biological cells is studied. A nonlinear, non‐local, dispersive, and space–time multiphysics model based on Maxwell's and asymptotic Smoluchowski's equations has been developed to calculate the transmembrane voltage and pore density on both plasma and nuclear membrane perimeters. The irregular cell shape has been modeled by incorporating in the numerical algorithm the analytical functions pertaining to Gielis curves. The dielectric dispersion of the cell media has been modeled considering the multi‐relaxation Debye‐based relationship. Two different irregular nucleated cells have been investigated and their response has been studied applying both the dispersive and non‐dispersive models. By a comparison of the obtained results, differences can be highlighted confirming the need to make use of the dispersive model to effectively investigate the cell response in terms of transmembrane voltages, pore densities, and electroporation opening angle, especially when irregular cell shapes and short electric pulses are considered. Bioelectromagnetics. 2019;40:331–342. © 2019 Wiley Periodicals, Inc.